Opinions of a group of students at ecci university on the inclusion of an exclusive frame for the modern languages program (2014)
This research was conducted with the goal of studying the general opinion, the interest, the possible contents and the feasibility on this project according to the 33 (32 students in the focus group and 33 students in the questionnaires) fifth semester students opinion of the evening shift of Modern Languages at ECCI University. Mostly aimed at detecting the position of the students in front of the inclusion of ICT as an aid to the process of formation, on Informational terms, allowing them to know the real environment to which they may face after graduation